Условия оптимальности в задачах управления системами дифференциальных уравнений с импульсными воздействиями при нелокальных краевых условиях - Шарифов, Я.А. (Український математичний журнал, 2012)
Дослiджується задача оптимального керування, в якiй стан керованої системи описується диференцiальними рiвняннями з iмпульсними збуреннями при нелокальних крайових умовах. Спочатку з допомогою принципу стиснутих вiдображень доведено iснування та єдинiсть розв’язкiв нелокальної крайової задачi при iмпульсних збуреннях i фiксованих допустимих керуваннях. При деяких умовах на початковi данi задачi обчислено градiєнт функцiонала i встановлено необхiднi умови оптимальностi. We investigate the problem of optimal control in which the state of the controlled system is described by impulsive differential equations with nonlocal boundary conditions, which is a natural generalization of the Cauchy problem. Using the principle of contracting mappings, we prove the existence and uniqueness of a solution of a nonlocal boundary-value problem with impulse perturbations and fixed admissible controls. Under certain conditions for the initial data of the problem, we calculate the gradient of a functional and obtain necessary optimality conditions.